Region-based segmental swapping of homologous enzymes for higher cadaverine production - Seungjin Kim; Dae-yeol Ye; Hyun Gyu Lim; Myung Hyun Noh; Jae-Seong Yang; Gyoo Yeol Jung (Microbial Cell Factories)
Abstract Background Cadaverine, displaying potential in medicine, agriculture and polyamide production, is biologically produced through L-lysine decarboxylation. Considering the potential of the polyamide market, its biological production has been focused on with following diverse efforts to improve the production. In Escherichia coli, lysine decarboxylase exists in two forms: CadA and LdcC, and it is known that CadA exhibits superior catalytic activity compared to LdcC. Despite its potential, cadaverine production is limited due to increased intracellular pH, which destabilizes the decameric structure of CadA and inhibits its activity. Results In this study, based on the structural analysis, a chimeric CadA enzyme, CL2, was engineered by replacing its pH-sensitive region with a structurally stable counterpart derived from LdcC. The resulting BLCL2 strain with CL2 produced 1.12 g/L of cadaverine—1.96 times higher than BLC strain with the wild type CadA in flask culture. Compared to the wild type CadA, structural modifications enhanced pH stability and improved the affinity of CadA toward pyridoxal 5-phosphate (PLP), its cofactor. Conclusions This study developed the improved strains for cadaverine production by creating the new enzyme, which is validated by enhanced amount of cadaverine. In addition, the segmental swapping guided by structure analysis was exhibited as the one of effective method in protein engineering strategies. These advancements offer a promising approach to optimizing cadaverine biosynthesis for industrial applications.